Development a Process of Technological Innovation for Industrial Paper Production - Alarcon Segovia, Lilian Celeste (2021)
Thispaper presents a description of an innovative process applied to theproduction of paper from the use of stem fibers of the banana plant.According to the Organization for Economic Co-operation andDevelopment Oslo Guidelines, innovation is essential for growth inproduction as well as productivity and is a continuous process thatmakes changes in products, processes and captures new knowledge. Inorder to guarantee product (paper) and process (pulp system)innovation, a comparison was made with the mechanical properties ofpaper obtained from the organic waste with a typed paper commercialuse wave produced in a paper industry located in Asunción-Paraguay.The temperature, time and reagents chemical were operationalvariables selected to comparison of innovative processes. The yieldof innovator process analyzed was 52.5%. The results of comparison ofprocesses for obtaining cellulosic pulp indicates that mechanicalproperties as Stress (N.m/g), Compression in the plane (N) andresistance to compression in the edge (N) increase in comparison withconventional processes (Chemical process to soda and ChemicalProcess Kraft ) and this properties are highly valued by the paperindustries for use in corrugating industries. The (pulp system)innovation process presents many technical and economic advantagesamong alternative processes for paper production.